European integration and disintegration : east and west - Bideleux, Robert; Taylor, Richard, 1946- (Routledge, 1996)
Europe has changed radically since 1989 and continues to change at great speed. This book deals with the principle problems and challenges confronting Europe in the aftermath of the Cold War and the collapse of European communism. Whilst endeavouring to strike a balance between East, West, North and South, the volume is more concerned with the changing political, economic and cultural morphology of Europe, and of the relations within it, than with the formal institutional arrangements of the European Community and its successor, the European Union. There are already numerous books on the institutional development of the EU, but relatively few with a wider compass and institutional interpretations of European integration. The book shows that the study of European integration should be taken in the round, avoiding a narrow and self-centered concern with the development of the 'lesser Europe' of the EU. It demonstrates that integration should be seen as neither an inexorable predetermined process, nor as an automatic consequence of high levels of economic interdependence, but rather as something that proceeds in fits and starts and sometimes suffers reverses.